Investing Artificial Intelligence For Arabic Learning/ استثمار الذكاء الاصطناعي في تعلم اللغة العربية - ‫Mohammed Ahmed Abou Adel (Ijaz Arabi Journal of Arabic Learning, 2022)
This research paper examines the two most recent and successful experiments using artificial intelligence to learn Arabic. After analyzing these distinctive experiences, we can use them to bypass the traditional methods of teaching Arabic and move on to benefit from the tremendous development witnessed by artificial intelligence. The most prominent advantages that characterize this contemporary learning are the consideration of integration and comprehensiveness in teaching Arabic with all its fundamental skills. It is flexible, active, asynchronous learning that helps raise the level of focus and attention by using attractive and enjoyable audio-visual effects. The research compares the two best apps on smartphones to show that they are distinguished from many other apps in following a scientific methodology in teaching Arabic in an interactive, fun, and simple way, with fundamental differences that express the uniqueness of each of them from the other. The most prominent feature of (the Buss app) is to allow Arabic language learners to communicate electronically with native speakers of the language, correct their pronunciation for free, or collaboratively share any information with them. While the (Arabits) app was distinguished from others by starting with teaching the Arabic alphabet and focusing on innovatively teaching letters exits using sound and illustrations for each letter.